2020
DOI: 10.1016/j.ijcard.2019.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation factors and fibrinolytic activity in the left atrial appendage and other heart chambers in patients with atrial fibrillation: is there a local intracardiac prothrombotic state? (HEART-CLOT study)

Abstract: Atrial fibrillation (AF), a risk factor for stroke and systemic thromboembolism, is associated with unfavorable fibrin clot properties and increased thrombus formation in peripheral blood. The left atrial appendage (LAA) is known to be the primary site of thrombus formation. Aim: We investigated the relative differences in plasma fibrin clot features including plasma fibrin clot permeability (K s ) and clot lysis time (CLT) between the right atrium (RA), right ventricle (RV), left atrium (LA), left ventricle (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 46 publications
1
29
1
Order By: Relevance
“…While the turbulent flow within the fibrillating atrial appendage is a primary risk factor for the development of a thrombus within the chamber, data suggests that the prothrombotic milieu within the appendage also potentiates thrombus formation (6, 7). Bartus et al illustrated that from direct sampling of blood from within the atrial appendage compared with sampling from other heart chambers revealed a local prothrombotic state with evidence of prolonged clot lysis time and reduced clot porosity (6). Others have also described increased levels of procoagulant factors within the atrial appendage compared with the right atrium and femoral vein, further supporting local activation of the coagulation system (7).…”
Section: Discussionmentioning
confidence: 99%
“…While the turbulent flow within the fibrillating atrial appendage is a primary risk factor for the development of a thrombus within the chamber, data suggests that the prothrombotic milieu within the appendage also potentiates thrombus formation (6, 7). Bartus et al illustrated that from direct sampling of blood from within the atrial appendage compared with sampling from other heart chambers revealed a local prothrombotic state with evidence of prolonged clot lysis time and reduced clot porosity (6). Others have also described increased levels of procoagulant factors within the atrial appendage compared with the right atrium and femoral vein, further supporting local activation of the coagulation system (7).…”
Section: Discussionmentioning
confidence: 99%
“…However, the American College of Cardiology/American Heart Association guidelines do not provide specific guidance on anticoagulation due to the lack of evidence. Discontinuation of oral anticoagulation may be considered in patients who are at increased risk of bleeding undergone successful surgical ablation of AF and LAA excision or exclusion and who remain in sinus rhythm for at least 3 months during which they have been anticoagulated ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, the LAAO procedure emerged as an alternative method for stroke prevention 17 . Multiple observational studies point to the feasibility and safety of percutaneous endocardial and epicardial LAAO procedures, and present long‐term effectiveness in thromboembolism and bleeding risk reduction, even in high‐risk patients 16,18‐20 .…”
Section: Discussionmentioning
confidence: 99%